2015
DOI: 10.1002/pds.3775
|View full text |Cite
|
Sign up to set email alerts
|

Reduced prevalence of chronic tubal inflammation in tubal pregnancies after levonorgestrel emergency contraception failure

Abstract: Purpose The aim of this study was to compare chronic fallopian tubal inflammatory disease and fibrosis between patients with general tubal pregnancy (TP) and TP with levonorgestrel (LNG) emergency contraception (EC) failure. Methods We retrospectively studied patients with general TP (n = 79) and TP following LNG-EC failure (n = 81) within the same conception cycle. Information on the gynecological features of each subject was collected. Pelvic inflammatory disease and associated sequelae were assessed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…It is reported that the serum CT-IgG positive antibody can be detected in women with ectopic pregnancy and normal pregnancy, and the rates are 32–71 and 4–39%, respectively. The relative risk of tubal pregnancy in women with serum CT-IgG positive is 2.4–7.9 ( 19 ). Dunne et al ( 20 ) studied and suggested that with the decline in CT infection positive rate, the incidence rate of ectopic pregnancy is also rapidly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the serum CT-IgG positive antibody can be detected in women with ectopic pregnancy and normal pregnancy, and the rates are 32–71 and 4–39%, respectively. The relative risk of tubal pregnancy in women with serum CT-IgG positive is 2.4–7.9 ( 19 ). Dunne et al ( 20 ) studied and suggested that with the decline in CT infection positive rate, the incidence rate of ectopic pregnancy is also rapidly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Tubal inflammation, which is typically secondary to genital infection, was generally regarded an important risk factor for EP, but we previously confirmed that tubal pregnancy following LNG-EC failure is associated with lower rates of Chlamydia trachomatis infection, fallopian tubal inflammation, and/or fibrosis compared with general tubal pregnancy [ 7 ]. Thus, we hypothesize that LNG, combined with a high progesterone level, might influence fallopian tube physiology rather than tubal morphology or salpingitis.…”
Section: Introductionmentioning
confidence: 96%